Bioinformatics Analysis of Xyloglucan Endotransglycosylase/Hydrolase (XTH) Gene from Developing Xylem of a Tropical Timber Tree Neolamarckia Cadamba - Tiong Shing, Yiing; Ho Wei, Seng; Pang Shek, Ling; Ismail, Jusoh (Science Publications, 2015)
This study reported the isolation and in silico characterization of a full-length Xyloglucan endotransglycosylase/Hydrolase (XTH) cDNA from Neolamarckia cadamba, an important tropical light hardwood plantation tree species. XTH is considered as a key agent to regulate cell wall expansion and is believed to be responsible for the incorporation of newly synthesised xyloglucan into the wall matrix. The full-length of NcXTH was firstly predicted using the XTH singletons from the NcdbEST through contig mapping approach. Further validation and confirmation were conducted by amplifying the full-length XTH cDNA using RT-PCR approach. Two fulllength XTH cDNAs, namely NcXTH1 (JX134619) and NcXTH2 (JX134620) were discovered and the nucleotide sequences were 893 and 1,024 bp in length, respectively. The open reading frames for NcXTH1 and NcXTH2 were 858 and 915 bp, respectively. Results predicted that NcXTH1 and NcXTH2 proteins carry out XET activity but they are from different XTH family members. This full-length NcXTH cDNA can serve as good candidate genes in association genetics study which leads to Gene-Assisted Selection (GAS) in the N. cadamba tree breeding programme.